Rekonseptualisasi Makna Jihad Melalui Kurikulum Di Pondok Pesantren Salaf Kabupaten Tegal - Mokhamad Miptakhul Ulum (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
The discussion of jihad is a very extrem theme. Wise people must be careful discuss it. The word jihad if expressed by someone in a speech can be dangerous because with that word can be people’s blood who should be respected, instead it flows. Some teachers of salaf islamic boarding school in Tegal Regency always be careful in discuss the concept of jihad. Their strategy is create a curriculum that is not to detailed. They not necessarily give a discussion of jihad to their students. The power of intellectual, spiritual and student mentality get the teacher’s attention in giving a discussion of jihad to theirs student. The intellectual power, spirituality and mentality of the santri are the concern of the teacher in giving discussion of jihad to his students. This research aims to deeply analyze the pattern of teaching carried out by salaf islamic boarding school teachers in Tegal Regency on the meaning of jihad. This type of research is field research and using a qualitative approach. The sources of this research is Nurul Huda Al-Mu’awanah Islamic Boarding School Danawarih Balapulang Tegal Regency. Methode of data collection is documentation, observation and interviews. The analysis used is descriptive field analysis. The result of this reserach is discussion of the meaning of jihad has new discourse that implemented throught the curriculum of salaf islamic boarding schools ini Tegal Regency, that is in the form of intellectual and spiritual cultivation as study, full respect for pancasila, red and white flag and traditional customs as well as doing self defense training, karate and pagar nusa.